Knowledge of stunting and balanced diet among nursing students - Anita Apriliawati; Titin Sutini; Medya Aprilia Astuti; Dayana Noprida; Ineke Kusuma Waluyo (Malahayati International Journal of Nursing and Health Science, 2024)
Background: Stunting is a chronic nutritional issue in children that remains a primary focus for the government to prevent and reduce its prevalence. Various efforts have been made in collaboration with various parties to improve the nutritional status of children aged 0-2 years, pregnant women, and before pregnancy (adolescent girls). The proper food composition for teenagers should adhere to the 'Fill my plate' principle with a composition of 1/3 staple food, 1/3 vegetables, 1/6 fruit, and the remaining 1/6 containing animal and vegetable protein. Good knowledge about balanced nutrition consumption in adolescent girls is essential to support the prevention of stunting in children in the future.Purpose: To identify the relationship between knowledge about stunting prevention and the consumption of balanced nutritious food in adolescent girls.Method: This research is an observational analytical quantitative study with a cross-sectional approach. The population in this study consisted of 95 female first-semester students at the Faculty of Nursing, Muhammadiyah University, Jakarta. The sampling technique used was purposive sampling with criteria being young female respondents aged 16-20 without chronic illnesses. The number of samples was 86. Data analysis used the chi-square statistical test to determine the relationship between knowledge about stunting prevention and the consumption of balanced nutritious food in young women.Results: The average age of respondents was 18 years, the average score for knowledge about stunting prevention was 26.6, the majority of teenagers had a very good knowledge category, with 65 people (75.5%), and the majority of teenagers consumed balanced nutrition, 48 people (55.8%). The results of the statistical test obtained a p-value of 0.26 (>0.05), which means there is no relationship between teenagers' knowledge about stunting and the consumption of balanced nutrition.Conclusion: It is hoped that healthcare professionals, especially nurses, can be involved and provide education and other interventions in preventing stunting by supporting young women to consume balanced nutrition.